Operation Moses: Evakuasi Massal Kaum Yahudi Ethiopia ke Israel Tahun 1984-1985 - Moh. Najmuddin; Maya Mustika Kartika Sari; Sukma Ayu Putri Ariningtyas; Adli Hazmi; Nur Diana Izzah; Imam Zarkachi (Batuthah: Jurnal Sejarah Padaban Islam, 2025)
The mass migration of Ethiopian Jews to Israel through mass evacuation occurred between 1984 and 1985. In 1984, hundreds of thousands to millions of Ethiopians fled to Sudan due to famine, persecution, and civil war that occurred in Ethiopia. This study focuses on answering the question of why the Israeli government is willing to accept the presence of Ethiopian Jews and how Israel conducts its intelligence operations in the midst of unfriendly countries. This study uses a historical method that focuses on the analysis of primary and secondary sources through four stages, namely Heuristics, Verification, Interpretation and Historiography. This study can be found that the Ethiopian Jewish Community is an ancient Jewish group that has inhabited Ethiopia for thousands of years. They are also called the Beta Israel (House of Israel) or Falasha (foreigners). The civil war, drought and discrimination experienced by Ethiopian Jews in the 1980s forced some of them to flee to Sudan and find a way to get to Israel. Likewise, the common identity has made the Israeli government willing to accept the presence of Ethiopian Jews in its country. Through intelligence and diplomacy facilitated by the United States, the Israeli government finally succeeded in bringing Ethiopian Jews to Israel from Sudan.